ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

A nasal vaccine candidate based on S2 and N proteins from SARS-CoV-2 generates a broad antibody response systemically and in the lower respiratory tract - Yadira Lobaina; Rong Chen; Dania Vazquez-Blomquist; Edith Suzarte; Miaohong Zhang; Zhiqiang Zhou; Yaqin Lan; Gerardo Guillen; Wen Li; Yasser Perera; Lisset Hermida (Immunologic Research, 2025)

The immunosuppressive landscape in tumor microenvironment - Wuyi Liu; Huyue Zhou; Wenjing Lai; Changpeng Hu; Rufu Xu; Peng Gu; Menglin Luo; Rong Zhang; Guobing Li (Immunologic Research, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

Potential therapeutic strategies for myocardial infarction: the role of Toll-like receptors - Sumra Komal; Nimrah Komal; Ali Mujtaba; Shu-Hui Wang; Li-Rong Zhang; Sheng-Na Han (Immunologic Research, 2022)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)